2014
DOI: 10.5430/jha.v3n4p37
|View full text |Cite
|
Sign up to set email alerts
|

An online short-term bed occupancy rate prediction procedure based on discrete event simulation

Abstract: In recent years, population growth and aging society impose large pressure on the resource requirement in Singapore public hospital system. Beds are one of the most critical resources in healthcare system. How to manage beds efficiently is an important and challenging task for the health service providers in any healthcare systems. One frequently used performance indicator of bed management is bed occupancy rate, which measures the bed utilization. In this paper, an online prediction procedure based on discret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Researchers in the UK have based their studies on the duration of stay of infants by analysing the duration of stay in premature infants, having been observed to be more intensive [31,13,32,33].…”
Section: Predicting the Length Of Staymentioning
confidence: 99%
“…Researchers in the UK have based their studies on the duration of stay of infants by analysing the duration of stay in premature infants, having been observed to be more intensive [31,13,32,33].…”
Section: Predicting the Length Of Staymentioning
confidence: 99%
“…Overlooked elements affected the demand for beds in the hospital per day. The researchers to understand and forecast the bed occupancy model like simulation (Developed using ARENA 10.0) and linear regression and simulation model is mostly preferred amongst all because it answers a lot about the availability and engagement of beds in a hospital [27,33].…”
Section: Bed Occupancymentioning
confidence: 99%
“…Zhecheng [10] proposed and developed an online prediction procedure based on discrete-event simulation to predict the bed occupancy rate in a short term period. Simulation results showed that the predicted values were closer to the actual values with a narrower confidence interval compared to the offline approach.…”
Section: Zhao and Liementioning
confidence: 99%